Pengaruh Potret Pemberdayaan Masyarakat Berbasis Aset Lokal pada Kelompok Budidaya Ikan Koi di Desa Banyuglugur Kecamatan Banyuglugur Situbondo - Nuril Endi Rahman (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2018)
Empowerment has recently become a keyword in any poverty alleviation programs, which is either conducted by the government or by any companies through CSR programs. Empowerment is closely related to potential, participation, and capacity enhancement, therefore it cannot be separated from the role of local institutions or local actors that exist inthe society, because of their function as the ‘driver’ in the empowerment. This study is aimed to comprehend the success of the empowerment program by the approach of the Koi fish farming groups’ asset growth in the village of Banyuglugur, especially during the empowerment process. The research used qualitative descriptive method and both the location and the informants were decided purposively to gain the samples. The data was collected by conducting observation, interviews, and documents study. The result showed that the success of the empowerment was achieved by the appliance of local asset-based approach, by local actors’ roles in encouraging the awareness of youth participation and in identifying the village potential collaboratively, and also by the proper cooperative factors between the Community Development Officer as the representative of PT PJB Paiton and the head of Karang Taruna Youth Local Organization. The word empowerment has recently become a key word in any poverty allevation program, be it a pro